Political Party Strategies in Recruiting Prospective Mayor and Deputy Mayor Candidates of Tegal 2024 - Fatkhi, Ariyandi Nur; Sutjiatmi, Sri; Sugiharto, Unggul (IHSA Institute, 2025)
Political recruitment is an important process in a democratic system, as it determines the figures who will lead the regional government. Various political parties are developing different strategies in this process, ranging from internal cadre recruitment to approaches towards external figures who are considered to have electoral appeal. This research uses a qualitative method with a descriptive approach, collecting data through in-depth interviews with the leaders of the PDIP, PKS, and Golkar political parties in Tegal City, as well as party documents related to the recruitment process. The theory used by the author employs the Political Recruitment theory from Gabriel Almond & Powel, which has two processes: open and closed. The theory is used to describe and analyze the recruitment patterns carried out by the three parties. The research results show that political parties adopt various strategies in recruiting candidates, such as strict selection through electability surveys, internal party consolidation to maintain unity, and collaboration with community groups to increase public support. Factors influencing recruitment strategies include the level of popularity, candidate acceptability, financial capability, and commitment to the party's vision and mission. This research concludes that the success of recruitment strategies does not only depend on the internal mechanisms of the party but also on the party's ability to adapt to the aspirations of the community and build a solid coalition